Integrating Kayuh Baimbai Philosophy into Project-Based Learning: Strengthening Social-Emotional Skills of Elementary Students in a Floating Market Community - Novi Suma Setyawati; Novi Nurdian; Armin Fani (Papanda Publisher, 2026)
Social-emotional skills are critical for 21st-century elementary education, yet conventional teaching methods in Indonesia inadequately facilitate their development, particularly through integration of local cultural values. This study explored the implementation of project-based learning (PjBL) integrated with the Kayuh Baimbai philosophy—a local wisdom emphasizing cooperation and collective responsibility—to strengthen social-emotional skills among elementary students in the Pasar Terapung Lokbaintan area, South Kalimantan. A qualitative case study approach was employed, involving two elementary schools, with data collected through semi-structured interviews with principals and teachers, classroom observations, and documentary evidence. Purposive sampling selected participants meeting inclusion criteria. Data analysis followed Miles, Huberman, and Saldaña's framework, with trustworthiness ensured through triangulation and member checking. The culturally grounded PjBL approach effectively enhanced students' empathy, responsibility, and cooperative behaviors through authentic project activities. Students demonstrated spontaneous prosocial behaviors, sophisticated understanding of collaborative principles, and improved conflict resolution skills. Unexpectedly, the approach fostered student agency and distributed leadership. Implementation challenges included limited preparation time, insufficient contextual materials, and variable parental engagement. Integrating local cultural philosophy into PjBL provides an effective mechanism for strengthening elementary students' social-emotional competencies while preserving indigenous knowledge. The study extends sociocultural learning theory and offers actionable pedagogical strategies for resource-constrained settings.